Evaluation on the Learning Management System Online Activities as Perceived by Grade 12 General Academic Strand, Students of Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study compared how two learning management systems (LMS), the Blackboard systemand bright space, are perceived by Bestlink College of the Philippines Grade 12 Generalacademic strand students; according to the report, using an LMS has advantages, includingmaking it simple to access shared data and files monitoring and recording studentperformance personalizing the learning experience and promotion dialogue.In terms of Module Content, the first variable shows a weighted mean of (2.76), and the verbalinterpretation is (Agree). The second variable is accessibility. The weighted mean is (2.84),and the verbal interpretation is (Agree). It came up by the following students and respondentsof this questionnaire.According to the survey, students who use the Brightspace system are more aware of thebenefits of e-learning than students who use the Blackboard system. According to the study,by selecting the proper strategies to promote sustainable teaching and learning, thesefindings can assist educators in adopting open and distance learning efficiently. As anevaluation strategy, the study uses developmental evaluation (DE), which provides a deeperdegree of analysis to comprehend the role.
Keywords: Education